Analysis of Differentially Expressed Genes in Necrotic Enteritis-infected Fayoumi Chickens using RNA Sequencing - Truong, Anh Duc (J Poult Sci, 2017)
We identified and evaluated differentially expressed genes (DEGs) by RNA-Sequencing (RNA-Seq) in the intestinal mucosa of two Fayoumi chicken lines, M5.1 and M15.2, that are affected by necrotic enteritis (NE); these chicken lines share the same genetic background but have different major histocompatibility complexes. RNA-Seq generated over 49 and 40 million reads for lines M5.1 and M15.2, respectively. The alignment of these sequences with the Gallus gallus genome database revealed the expression of more than 14,500 genes in two lines, among which 581, 1270, and 1140 DEGs were detected when lines M15.2 and M5.1 were compared with the control and compared between each other. The analysis of all DEGs using the gene ontology database revealed annotations for 111 biological processes, 32 cellular components, and 17 molecular functions, and KEEG pathway mapping indicated that the DEGs were primarily involved in immunity, responses to various stimuli, and signal transduction. In addition, we analyzed 183 innate immune genes that were differentially expressed in NE-induced chicken lines, including 46 CD molecular genes, 89 immune-related genes, and 13 β-defensin genes with 3 lineage-specific duplications. Taken together, the transcriptional profiles showed that line M5.1 was more resistant to NE than line M15.2 and that differential gene expression patterns were associated with host genetic differences in resistance to NE. qRT-PCR and RNA-Seq analyses showed that all the genes examined had similar responses to NE (correlation coefficient R=0.84 to 0.88, p<0.01) in both lines. To the best of our knowledge, this is the first study that describes NE-induced DEGs using RNA-seq in two lines with different levels of susceptibility to NE. These results will lead to increased insights on NE disease resistance mechanisms and the role of host genes in the control of the host immune response.